KONSEP PENDIDIKAN ISLAM DALAM PERSPEKTIF K.H. AHMAD DAHLAN - Putra, Dhian Wahana (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
Education has become a "trademark" in Muhammadiyah movement, as a concrete form of the role of Muhammadiyah in empowering Muslims and the intellectual minds of the nation. Discussion of Muhammadiyah-based education cannot be separated from the figure of K.H. Ahmad Dahlan, involving the focus of ultimate truth to capture what was implicit in Al-Manaar's interpretation so that although he did not have a western education, he was able to open the gate of rationality through the teachings of Islam itself, which was called ijtihad. By rejecting taqlid. KH. Ahmad Dahlan can be regarded as a "model" in the generation of revival which is a "central point" of a movement that appears to overcome the challenges facing Islam in the form of backwardness and stagnation in the Islamic educational system. Unlike a number of national figures in his days who were more concerned with political and economic issues, K.H. Ahmad Dahlan devoted himself fully in the field of education. Based on this description, this study aimed to investigate the concept of Islamic education from KH. Ahmad Dahlan’s perspectives. In particular, the direction of this study was to understand the goals of Islamic education according to K.H. Ahmad Dahlan, the conceptualisation of Islamic education curriculum according to K. Ahmad Dahlan, as well as the methods of Islamic educational practice according to K. AH Ahmad Dahlan. The study was library research with the technique for data collection including documentation conducted through looking for data about things or variables in the form of notebook transcripts, newspapers, magazines, inscriptions, minutes, meetings, agendas, and so on. Data analysis were carried out through descriptive analysis. The findings of this study revealed that the perspectives of KH. Ahmad Dahlan about Islamic education: first, the aim of Islamic education is to maintain the purity of human beings; second, the curriculum is integral; third, and the method of hiwar/repetition, balance and proportionality between theory and practice was used.